Development of a novel molecular probe for visualizing mesothelin on the tumor via positron emission tomography. - He, Yingfang; Kong, Jinping; Wang, Ze; Zhang, Yu; Qing, Tingting; Xie, Fang; Chen, Tengxiang; Han, Junbin (European Journal of Nuclear Medicine & Molecular Imaging, 2025)
Objectives: Mesothelin (MSLN) is an antigen that is overexpressed in various cancers, and its interaction with tumor-associated cancer antigen 125 plays a multifaceted role in tumor metastasis. The serum MSLN expression level can be detected using enzyme-linked immunosorbent assay; however, non-invasive visualization of its expression at the tumor site is currently lacking. Therefore, the aim of this study was to develop a molecular probe for imaging MSLN expression through positron emission tomography (PET). Methods: VHH 269-H4 was obtained via immunization of llama using a fragment of MSLN from residue 360 to residue 597. S-2-(4-isothiocyanatobenzyl)-1,4,7-triazacyclononane-1,4,7-triacetic acid (p-SCN-Bn-NOTA) was conjugated to VHH 269-H4 to yield precursor NOTA 269-H4 for radiolabeling. The chelator-to-VHH ratio was determined by mass spectrometry. The binding kinetics of VHH 269-H4 and NOTA 269-H4 were measured by surface plasmon resonance. Flow cytometry was carried out using the anti-mesothelin monoclonal antibody Anetumab to select MSLN-positive and MSLN-negative cell lines. After radiolabeling, the radiochemical purity and in vitro stability were tested by radio-thin-layer chromatography and size exclusion chromatography, respectively. A saturation binding assay was conducted to measure the dissociation constant (Kd) of [68Ga]Ga-NOTA-269-H4. By mircoPET/CT imaging and biodistribution studies, the in vivo performances of the novel tracer were investigated in NCG mice bearing OVCAR-8, SKOV-3, or patient-derived xenografts. Results: VHH 269-H4 targeting MSLN was obtained with a Kd value of 0.3 nM. After conjugation, approximately 27% and 3.2% of VHH were coupled to one and two NOTA chelators, respectively. This yielded precursor NOTA 269-H4 with a Kd value of 1.1 nM. The radiochemistry was accomplished with moderate radiochemical yields (34 ± 14%, n = 9, decay-corrected). [68Ga]Ga-NOTA-269-H4 was obtained with high radiochemical purity (> 99%), and was stable after 90 min incubation at room temperature. The binding affinity of the radioligand towards MSLN was kept in the nanomolar range. Flow cytometry revealed that OVCAR-8 cells possess a high level of MSLN expression, while MSLN expression on SKOV-3 cells was negligible. Consistently, in microPET/CT imaging, [68Ga]Ga-NOTA-269-H4 demonstrated clear tumor visualization using NCG mice bearing OVCAR-8 xenografts, but no radioactivity accumulation was observed in SKOV-3 xenografts, suggesting a high specificity of the tracer in vivo. In biodistribution studies, [68Ga]Ga-NOTA-269-H4 displayed radioactivity accumulation of 2.93 ± 0.39%ID/g in OVCAR-8 xenografts at 30 min post-injection, and the highest tumor-to-blood ratio (~ 3) was achieved at 90 min post-injection. In NCG mice bearing patient-derived xenografts, [68Ga]Ga-NOTA-269-H4 was able to noninvasively detect MSLN expression via microPET/CT imaging. Conclusions: To our knowledge, our studies achieved the first-time to non-invasively detect MSLN expression clearly using a single domain antibody fragment. To sum up, [68Ga]Ga-NOTA-269-H4 is a highly promising PET probe to visualize MSLN expression in vivo and holds great potential to monitor MSLN expression during tumor development.